Good business practices in Ecuador. Year 2021 - Abendaño Ramírez, Mónica; Guamán Guadalima, Nelly; Vayas Ruiz, Eliza (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
To know the good ethical practices, an exploratory-descriptive study was carried out, based on a mixed approach methodology, divided into two stages. In the first of a qualitative nature, an in-depth interview was applied, and in the second, the data collection instrument was proposed: the survey. The population under study was defined, according to the Merco ranking (Business Monitor of Corporate Reputation), considering an intentional sample of 20 companies in Ecuador. The conclusions corroborated that the values in the context of the organization are the basis of the organizational culture, which guide their actions.